How does brand legitimacy shapes brand authenticity and tourism destination loyalty: Focus on cultural heritage tourism - Xiaohua Chen; Gyehee Lee (Global Business & Finance Review (GBFR), 2021)
Purpose: The existing cultural heritage tourism research rarely pays attention to the antecedents of brand authenticity. This research fills this gap and points out the critical role of brand legitimacy in building destination loyalty by constructing a theoretical framework. Design/methodology/approach: This study collected 436 valid samples through an online questionnaire survey in China. The respondents were adults over 18 years old who have visited cultural heritage tourism destinations in the past year. This research used a combination of SPSS and AMOS statistical software to examine the theoretical model. Findings: The empirical analysis results showed that the tourist destination's brand legitimacy positively impacts the three dimensions (consistency, credibility, and originality) of the destination brand authenticity. At the same time, brand authenticity positively affects the perceived value, and brand trust positively impacts. Moreover, brand authenticity has a mediating impact on the relationship between brand legitimacy and perceived value and the relationship between brand legitimacy and brand trust. Similarly, perceived value and brand trust also play a mediating role in the relationship between brand authenticity and tourism destination loyalty. Research limitations/implications: This research emphasized the importance of historical inheritance and puts forward specific theoretical and practical enlightenment for heritage tourism from the perspective of brand legitimacy management. However, there are still some research limitations. Future research could expand the research samples to other countries and utilize a more systematic data collection method. Then, the measurement tool of brand legitimacy can also be explored from multiple dimensions. Originality/value: Readers of this paper can understand that brand legitimacy is a necessary but seldom discussed driving factor of authenticity related to heritage tourism. And discussing their positive influence on tourists' loyalty can make readers and destination managers better understand tourists' behavior in brand management.
Keywords: 650; Brand legitimacy; Legitimacy theory; Brand authenticity; Brand trust; Cultural heritage tourism